2022
DOI: 10.1021/acs.jpclett.2c02815
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Light–Matter Interaction on Efficiency of Quantum-Dot Light-Emitting Diodes

Abstract: Light–matter interaction can affect the radiative decay rate of excitons and thus the emission quantum yield (QY) of quantum dots (QDs). In this work, light–matter interaction and outcoupling efficiency of QD light-emitting diodes with different structures are investigated experimentally and theoretically. We show that the external quantum efficiency (EQE) of top-emitting devices is higher than that of the bottom-emitting devices, which is mainly due to the stronger light–matter interaction and higher light ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For conventional bottom‐emitting device structures shown in Figure a, the emitted light from QDs is coupled to different modes including: (1) air mode, in which light is emitted directly into the air; (2) substrate mode, where light is confined within the substrate due to TIR at the interface between substrate and air; (3) waveguide mode, where light is confined to the QLED thin film due to TIR at the interface between ITO and substrate glass; and (4) surface plasmon polariton (SPP) mode, where light propagate along the organic/metal interface and is coupled with the oscillation of free electrons in the metal. The percentage of each mode can be calculated by using a classical dipole radiation model, as we reported previously [ 160,161 ] for example, for a QLED with the structure of Glass/ITO/PEDOT:PSS/TFB/R‐QD/ZnMgO/Al (Figure 12b), the calculated power dissipation spectrum is shown in Figure 12c. Based on the values of in‐plane wavevector u, we can separate the four optical channels of QLED from left to right: air mode, substrate mode, waveguide mode, and surface plasmons, respectively.…”
Section: Recent Discoveries On Device Mechanismsmentioning
confidence: 99%
“…For conventional bottom‐emitting device structures shown in Figure a, the emitted light from QDs is coupled to different modes including: (1) air mode, in which light is emitted directly into the air; (2) substrate mode, where light is confined within the substrate due to TIR at the interface between substrate and air; (3) waveguide mode, where light is confined to the QLED thin film due to TIR at the interface between ITO and substrate glass; and (4) surface plasmon polariton (SPP) mode, where light propagate along the organic/metal interface and is coupled with the oscillation of free electrons in the metal. The percentage of each mode can be calculated by using a classical dipole radiation model, as we reported previously [ 160,161 ] for example, for a QLED with the structure of Glass/ITO/PEDOT:PSS/TFB/R‐QD/ZnMgO/Al (Figure 12b), the calculated power dissipation spectrum is shown in Figure 12c. Based on the values of in‐plane wavevector u, we can separate the four optical channels of QLED from left to right: air mode, substrate mode, waveguide mode, and surface plasmons, respectively.…”
Section: Recent Discoveries On Device Mechanismsmentioning
confidence: 99%
“…The thicknesses of the PTLs were optimized to tune the cavity length so that constructive interference at a spe-cific wavelength can occur. By using a classical dipole model that simultaneously considers the interference, the emitter orientations and the effect of Purcell factor on radiative decay rate of excitons, [24][25][26] the optimal OCEs of BE QLEDs and TE QLEDs, as well as the percentage of light distribution channels, can be accurately calculated, as shown in Figure 1b. At an optimal condition, the TE QLEDs exhibit an OCE of 45.74%, which is more efficient than 41.42% of BE QLEDs.…”
Section: Comparison Of Oce Between Te Qleds and Be Qledsmentioning
confidence: 99%
“…Reproduced with permission. [ 86 ] Copyright 2022, American Chemical Society. d) Purcell factor depending on the wavelength, CL thickness, and ETL thickness.…”
Section: Optimizationmentioning
confidence: 99%
“…[ 85 ] In 2022, Tian et al compared the effect of light–matter interactions in BQLEDs and TQLEDs to prove the efficiency of TQLEDs. [ 86 ] An optical modeling was performed to calculate the total dissipation power, where the F ( λ ) based on various cavity thicknesses was obtained for both devices. The results revealed that optimizing the cavity thickness can increase the F ( λ ) of QLEDs to 1.7 (Figure 3b), which was additionally supported by the facilitated trPL decay of TQLEDs (Figure 3c).…”
Section: Optimizationmentioning
confidence: 99%
See 1 more Smart Citation